# How do you use the chain rule to differentiate #root9(-cosx)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate √9(-cos(x)) using the chain rule, follow these steps:

- Let u = -cos(x).
- Find the derivative of u with respect to x: du/dx = sin(x).
- Let v = √9u.
- Find the derivative of v with respect to u: dv/du = 1/2(9u)^(-1/2) = 1/(2√9u) = 1/(6√u).
- Apply the chain rule: dv/dx = dv/du * du/dx.
- Substitute back u = -cos(x) and simplify the expression to get the final answer.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you find #dy/dx# by implicit differentiation given #y=sqrt(xy+1)#?
- How do you implicitly differentiate #tan(x+y) = x#?
- How do you use the quotient rule to show that #1/f(x)# is decreasing given that f(x) is a positive increasing function defined for all x?
- How do you differentiate #f(x)= e^(2x)* (x^2 - 4) *ln x# using the product rule?
- How do you find derivative of #f(x)=cosh(lnx)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7